The Role of Virtual Laboratories in Project-Based Learning for Sustainable Development Topics in Biology: A Systematic Literature Review - Muhammad Fuad; Risqah Amaliah Kasman; Rahmania Rahman; Muh. Alham Satnur; Herwandi; Armin Arif; A. Rahmatia (Postgraduate, University of Mataram, 2026)
This study aims to analyze the role of virtual laboratories in project-based learning (PjBL) on biology topics related to sustainable development through a Systematic Literature Review (SLR). The review was conducted following the PRISMA 2020 framework by examining articles published between 2013 and 2025 across major databases, including Scopus, Web of Science, ScienceDirect, ERIC, and Google Scholar. Inclusion criteria focused on studies integrating virtual laboratories, PjBL, and sustainability-related topics in biology education. The selection process identified one core study and several supporting studies relevant to the research objectives. The findings reveal that virtual laboratories function as effective enablers of PjBL by facilitating authentic scientific inquiry, especially in contexts with limited access to physical laboratory resources. Additionally, virtual laboratories contribute to improved conceptual understanding, scientific reasoning, and procedural skills. In terms of sustainable development, virtual laboratories promote resource efficiency and support the development of sustainability competencies, such as systems thinking and problem-solving. Despite these benefits, the limited number of integrated studies indicates a gap in empirical research. Overall, virtual laboratory–supported PjBL demonstrates strong potential for advancing innovative, sustainable, and competency-oriented biology learning.